Minimizing the risk of chemically reactive metabolite formation of new drug candidates: implications for preclinical drug design. Issue 5 (May 2017) - Brink, Andreas; Pähler, Axel; Funk, Christoph; Schuler, Franz; Schadt, Simone
Graphical abstract: Highlights: Reactive metabolite formation has been linked to drug-induced toxicity. Avoidance strategy widely applied in industry at early stages of drug discovery. In vitro assays support rational drug design for optimized compounds. Glutathione adduct formation predictive of covalent binding potential. Covalent binding successfully reduced for Roche clinical candidates of last decade. Abstract : Many pharmaceutical companies aim to reduce reactive metabolite formation by chemical modification at early stages of drug discovery. A practice often applied is the detection of stable trapping products of electrophilic intermediates with nucleophilic trapping reagents to guide rational structure-based drug design. This contribution delineates this strategy to minimize the potential for reactive metabolite formation of clinical candidates during preclinical drug optimization, exemplified by the experience at Roche over the past decade. For the majority of research programs it was possible to proceed with compounds optimized for reduced covalent binding potential. Such optimized candidates are expected to have a higher likelihood of succeeding throughout the development processes, resulting in safer drugs.